1989
DOI: 10.1073/pnas.86.12.4741
|View full text |Cite
|
Sign up to set email alerts
|

Fc-receptor and M-protein genes of group A streptococci are products of gene duplication.

Abstract: The partial nucleotide sequence for an Fcreceptor gene from an M-type 76 group A streptococcus was determined. DNA sequence analysis revealed considerable sequence similarity between the Fc-receptor and M-protein genes in their proposed promoter regions, signal sequences, and 3' termini. Additional analysis indicated that the deduced Fc-receptor protein contains a proline-rich region and membrane anchor region highly similar to that of M protein. (7). We previously reported the cloning and expression of an Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
1
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 41 publications
2
106
1
1
Order By: Relevance
“…In support of this model, the sequences upstream offcrA are similar to those upstream of emml2 (21), and the sequences downstream of ennX are similar to the sequences downstream of emm24. Furthermore, scpA is linked to emml2 (7) and is also just downstream of ennX.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In support of this model, the sequences upstream offcrA are similar to those upstream of emml2 (21), and the sequences downstream of ennX are similar to the sequences downstream of emm24. Furthermore, scpA is linked to emml2 (7) and is also just downstream of ennX.…”
Section: Discussionsupporting
confidence: 55%
“…Heath and Cleary (20) report that a type II IgG Fc receptor gene (fcrA) is present in a type 76 (OF-positive) streptococcal strain. These authors show thatfcrA contains sequences similar to M protein genes and is located in the same chromosomal position as emml2, as judged by upstream sequence similarities (21). Heath also reports (Ph.D thesis, University of Minnesota, Minneapolis, 1988) that the M76 gene is situated just downstream offcrA.…”
Section: Discussionmentioning
confidence: 80%
“…Sequencing of the genes for several Ig-binding cell surface proteins of S. pyogenes has shown that these molecules are also members of the M protein family (Frithz et al, 1989;Heath & Cleary, 1989;Gomi et al, 1990;Bessen & Fischetti, 1992;O'Toole et al, 1992). Some of these Ig-binding proteins have C repeats, like the classical M proteins, while others have a different type of repeat, the A repeat, in the central part of the sequence.…”
Section: Introductionmentioning
confidence: 99%
“…M proteins bind several human plasma proteins like fibrinogen (3), IgG (4,5), and regulatory proteins of the complement system (6,7). The binding activities of M proteins have been proposed to be of importance for the antiphagocytic activity of these proteins (2, 6 -9).…”
mentioning
confidence: 99%